Polymer composition and molded body
Patent Information
- Application Number
- JP2023136444
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-03-07
AI Technical Summary
【0010】 本発明によれば、4-メチル-1-ペンテン単独重合体の有する高い剛性(例:引張破壊応力および引張弾性率)等の物性を維持したまま、伸度の高い重合体組成物および成形体を提供することができる。
Smart Images

Figure 2025030813000001 
Figure 2025030813000002 
Figure 2025030813000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer composition and a molded article. [Background technology]
[0002] 4-Methyl-1-pentene polymers and polymer compositions containing the polymers are widely used in various applications because of their excellent heat resistance, releasability, chemical resistance, and the like. As such a 4-methyl-1-pentene polymer, for example, Patent Document 1 discloses a 4-methyl-1-pentene polymer having specific physical properties, and also discloses a polymer composition containing the polymer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2017 / 150265 Summary of the Invention [Problem to be solved by the invention]
[0004] Furthermore, homopolymers of 4-methyl-1-pentene have high rigidity and excellent heat resistance, and are therefore used in a variety of applications. Thus, although the homopolymer of 4-methyl-1-pentene has high rigidity, it has low elongation, and there are problems with its moldability into various molded articles and the fragility of the obtained molded articles, and there is room for improvement in this regard.
[0005] For example, in order to improve the elongation of the resulting molded article in a polymer composition containing 4-methyl-1-pentene homopolymer, it is conceivable to add a 4-methyl-1-pentene copolymer having a high comonomer content. However, it has been found that the use of such a copolymer reduces the rigidity and the properties of the 4-methyl-1-pentene homopolymer are lost.
[0006] The present invention has been made in view of the above, and an object of the present invention is to provide a polymer composition and a molded article having high elongation while maintaining the rigidity of a 4-methyl-1-pentene homopolymer. [Means for solving the problem]
[0007] As a result of extensive research into solving the above problems, the present inventors have found that the above problems can be solved by the following configuration examples, and have completed the present invention. A configuration example of the present invention is as follows.
[0008] [1] 75 to 85 mass% of a 4-methyl-1-pentene polymer (A) satisfying the following requirements (Ai) to (A-iii); 15 to 25 mass % of a 4-methyl-1-pentene polymer (B) satisfying the following requirements (Bi) to (B-iv); (wherein the total of polymers (A) and (B) is 100 mass %). Requirement (Ai): Consists of only structural units derived from 4-methyl-1-pentene Requirement (A-ii): Intrinsic viscosity [η] measured in decalin at 135°C A is 1.0-5.0 dl / g Requirement (A-iii): 13 Meso-dyad fraction (m A ) is greater than 97.0% Requirement (Bi): Consists of only structural units derived from 4-methyl-1-pentene Requirement (B-ii): Intrinsic viscosity [η] measured in decalin at 135°C B is 0.05 to 1.0 dl / g Requirement (B-iii): 13 Meso-dyad fraction (m B ) is 90.0-97.0% Requirement (B-iv): Melting point (Tm B ) is less than 220℃
[0009] [2] A molded article formed from the polymer composition (X) according to [1]. [3] The molded article according to [2], which is an injection molded article, an injection stretch blow molded article or an extrusion molded article. [4] The molded article according to [2] or [3], which is a film or a container. Effect of the Invention
[0010] According to the present invention, it is possible to provide a polymer composition and a molded article having high elongation while maintaining the physical properties such as high rigidity (e.g., tensile stress at break and tensile modulus) of a 4-methyl-1-pentene homopolymer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The various compounds that are raw materials for the following polymers (A) to (B) and other components may be compounds derived from fossil raw materials or compounds derived from biomass. Also, compounds derived from fossil raw materials and compounds derived from biomass may be used as raw materials for the following polymers (A) to (B) and other components.
[0012] ≪Polymer composition (X)≫ The polymer composition (X) according to the present invention (hereinafter also simply referred to as "composition (X)") is 75 to 85 mass% of a 4-methyl-1-pentene polymer (A) satisfying the following requirements (Ai) to (A-iii); 15 to 25 mass % of a 4-methyl-1-pentene polymer (B) satisfying the following requirements (Bi) to (B-iv); (wherein the total of polymers (A) and (B) is 100 mass %). Requirement (Ai): Consists of only structural units derived from 4-methyl-1-pentene Requirement (A-ii): Intrinsic viscosity [η] measured in decalin at 135°C A is 1.0-5.0 dl / g Requirement (A-iii): 13 Meso-dyad fraction (m A ) is greater than 97.0% Requirement (Bi): Consists of only structural units derived from 4-methyl-1-pentene Requirement (B-ii): Intrinsic viscosity [η] measured in decalin at 135°C B is 0.05 to 1.0 dl / g Requirement (B-iii): 13 Meso-dyad fraction (m B ) is 90.0-97.0% Requirement (B-iv): Melting point (Tm B ) is less than 220℃
[0013] The reason why such a composition (X) exhibits the above-mentioned effects is not necessarily clear, but it is believed that this is due to the use of a predetermined amount of a low stereoregular polymer (B) together with a high stereoregular polymer (A).
[0014] <4-methyl-1-pentene polymer (A)> The polymer (A) is a 4-methyl-1-pentene homopolymer satisfying the following requirements (A-ii) to (A-iii). The polymer (A) used in the composition (X) may be one type or two or more types.
[0015] Requirement (A-ii): Intrinsic viscosity [η] measured in decalin at 135°C A is 1.0-5.0 dl / g The intrinsic viscosity [η] A is preferably 1.2 to 4.5 dl / g, more preferably 1.5 to 4.0 dl / g. Intrinsic viscosity [η] A By using the polymer (A) having a molecular weight of 1.0 or less in the above range, the flowability during molding is improved, and a molded product having high transparency can be easily formed. The intrinsic viscosity [η] in this specification is specifically measured by the method described in the following examples. The intrinsic viscosity [η] can be adjusted, for example, by adjusting the polymerization conditions and / or the melt-kneading conditions.
[0016] Requirement (A-iii): 13 Meso-dyad fraction (m A ) is greater than 97.0% The mesodiad fraction (m A ) is preferably 97.5% or more, more preferably 98.0% or more, and although there is no particular upper limit, it is preferably 99.9% or less. Mesodiad fraction (m A By using the polymer (A) having a ratio of 1:1 to 1:1, a molded article having sufficient properties such as heat resistance and rigidity can be easily formed. The meso dyad fraction (m) in this specification is specifically measured by the method described in the examples below. The mesodyad fraction (m) is sometimes called isodyad isotacticity or mesodyad isotacticity. The mesodiad fraction (m) can be adjusted, for example, by the type of olefin polymerization catalyst described later.
[0017] The melting point (Tm) of polymer (A) measured by DSC A ) is preferably 220 to 250°C, more preferably 220 to 245°C. Melting point (Tm A By using the polymer (A) having a ratio of 1:1 to 1:1, a molded article having excellent heat resistance can be easily formed. The melting point (Tm) in this specification is specifically measured by the method described in the Examples below. The melting point (Tm) can be adjusted, for example, by the type of olefin polymerization catalyst described later.
[0018] The content of polymer (A) in composition (X) is 75 to 85 mass%, preferably 76 to 84 mass%, and more preferably 77 to 83 mass%, relative to 100 mass% of the total of polymers (A) and (B). When the content of polymer (A) is within the above range, a polymer composition and a molded article having high elongation can be easily obtained while maintaining the physical properties such as high rigidity (e.g., tensile stress at break and tensile modulus) possessed by polymer (A).
[0019] <Method of synthesizing polymer (A)> The polymer (A) can be obtained, for example, by polymerizing 4-methyl-1-pentene in the presence of an olefin polymerization catalyst described below. The polymerization can be carried out by any of liquid phase polymerization methods such as solution polymerization and suspension polymerization, or gas phase polymerization methods. The polymerization conditions and the like can be those described in WO 2014 / 050817. Conditions for synthesizing the polymer (A) that satisfies the above requirements (A-ii) to (A-iii) include, in particular, adjusting the polymerization temperature to 50 to 150°C and adjusting the amount of hydrogen added in the system to 0.00001 to 100 NL per mole of 4-methyl-1-pentene.
[0020] [Olefin polymerization catalyst] The olefin polymerization catalyst includes A bridged metallocene compound (a), At least one compound (b) selected from an organometallic compound (b-1), an organoaluminum oxy compound (b-2), and a compound (b-3) which reacts with the compound (a) to form an ion pair; A catalyst comprising: The olefin polymerization catalyst preferably further contains a support (c), and may further contain an organic compound component (d) as necessary.
[0021] Bridged metallocene compounds (a) The compound (a) is preferably a compound represented by the following formula [a1], and more preferably a compound represented by the following formula [a2]. Specific examples of compound (a) include the compounds described in WO 2014 / 050817 and WO 2017 / 150265.
[0022] [ka]
[0023] In formula [a1], M is a transition metal atom of Group 4 of the periodic table, for example, a titanium atom, a zirconium atom, or a hafnium atom; Q is selected from the group consisting of halogen atoms, hydrocarbon groups, neutral conjugated or non-conjugated dienes having 10 or less carbon atoms, anionic ligands, and neutral ligands capable of coordinating with lone pairs of electrons, in any combination, whether the same or different; j is an integer from 1 to 4; R A and R B are mononuclear or polynuclear hydrocarbon residues which may be the same or different and can form a sandwich structure together with M, Y is a carbon atom or a silicon atom; R C and R D may be the same or different and are selected from a hydrogen atom, a hydrocarbon group, a silicon-containing group, a halogen atom and a halogen-containing hydrocarbon group, and may be bonded to each other to form a ring.
[0024] [ka]
[0025] In formula [a2], R 1 is a hydrocarbon group, a silicon-containing group, or a halogen-containing hydrocarbon group, R 2 ~R 10 are selected from a hydrogen atom, a hydrocarbon group, a silicon-containing group, a halogen atom and a halogen-containing hydrocarbon group, may be the same or different, and may be bonded to each other to form a ring, M is a transition metal atom of Group 4 of the periodic table; Q is selected from the group consisting of halogen atoms, hydrocarbon groups, neutral conjugated or non-conjugated dienes having 10 or less carbon atoms, anionic ligands, and neutral ligands capable of coordinating with lone pairs of electrons, in any combination, whether the same or different; j is an integer from 1 to 4.
[0026] A compound (b), a carrier (c) and an organic compound component (d) The carrier (c) may be, for example, an inorganic or organic compound, and may be a granular or fine particle solid. The compound (a) is preferably used in a form supported on the carrier (c). The organic compound component (d) is used as necessary for the purpose of improving the polymerization performance and the physical properties of the resulting polymer, etc. Examples of the organic compound component (d) include alcohols, phenolic compounds, carboxylic acids, phosphorus compounds, amides, polyethers, and sulfonates.
[0027] Examples of the compound (b), carrier (c) and organic compound component (d) include the compounds, carriers and organic compound components described in WO 2014 / 050817, JP 2015-183141 A and WO 2014 / 123212. As the carrier (c), carriers described in WO 2010 / 055652, WO 2011 / 142400, WO 2013 / 146337, and JP 2015-74645 A can also be used.
[0028] <4-Methyl-1-pentene polymer (B)> The polymer (B) is a 4-methyl-1-pentene homopolymer satisfying the following requirements (B-ii) to (B-iv). The polymer (B) used in the composition (X) may be one type or two or more types.
[0029] Requirement (B-ii): Intrinsic viscosity [η] measured in decalin at 135°C B is 0.05 to 1.0 dl / g The intrinsic viscosity [η] Bis preferably 0.05 to 0.9 dl / g, and more preferably 0.05 to 0.8 dl / g. Intrinsic viscosity [η] B By using the polymer (B) having a molecular weight of 0.01 to 0.50, a composition (X) having high elongation can be easily obtained.
[0030] Requirement (B-iii): 13 Meso-dyad fraction (m B ) is 90.0-97.0% The mesodiad fraction (m B ) is preferably 90.5 to 96.5%, more preferably 91.0 to 96.0%. Mesodiad fraction (m B By using a polymer (B) having a molecular weight of 100 or more and a molecular weight of 100 or more, which falls within the above range, a composition (X) having high elongation can be easily obtained.
[0031] Requirement (B-iv): Melting point (Tm B ) is less than 220℃ The melting point (Tm B ) is preferably 150°C or higher and lower than 220°C, more preferably 160°C or higher and lower than 220°C. Melting point (Tm B By using the polymer (B) having a molar ratio (R) of 1:1 or more and 1:2 or more, a composition (X) having high elongation can be easily obtained, and a molded product having excellent heat resistance can be easily formed.
[0032] The content of polymer (B) in composition (X) is 15 to 25 mass%, preferably 16 to 24 mass%, and more preferably 17 to 23 mass%, relative to 100 mass% of the total of polymers (A) and (B). When the content of polymer (B) is within the above range, a polymer composition and a molded article having high elongation can be easily obtained while maintaining the physical properties such as high rigidity (e.g., tensile stress at break and tensile modulus) possessed by polymer (A).
[0033] <Method of synthesizing polymer (B)> The polymer (B) can be obtained, for example, by polymerizing 4-methyl-1-pentene in the presence of the above-mentioned olefin polymerization catalyst. The polymerization can be carried out by any of liquid phase polymerization methods such as solution polymerization and suspension polymerization, or gas phase polymerization methods. The polymerization conditions and the like can be those described in WO 2014 / 050817. Conditions for synthesizing the polymer (B) that satisfies the requirements (B-ii) to (B-iv) include, in particular, adjusting the polymerization temperature to 50 to 150°C and adjusting the amount of hydrogen added in the system to 0.00001 to 100 NL per mole of 4-methyl-1-pentene.
[0034] <Other ingredients> The composition (X) may be a composition consisting of only the polymers (A) and (B). However, depending on the application, the composition may contain other components, such as polymers other than the polymers (A) and (B) and resin additives, within the scope of not impairing the effects of the present invention. These other components may each be used alone or in combination of two or more.
[0035] Examples of the other polymers include thermoplastic resins described in WO 2018 / 179619.
[0036] Examples of the resin additives include (transparent) nucleating agents, antiblocking agents, pigments, dyes, fillers, lubricants, plasticizers, release agents, antioxidants, flame retardants, UV absorbers, antibacterial agents, surfactants, antistatic agents, weather stabilizers, heat stabilizers, antislip agents, foaming agents, crystallization aids, antifogging agents, antiaging agents, hydrochloric acid absorbers, impact improvers, crosslinking agents, co-crosslinking agents, crosslinking aids, adhesives, softeners, and processing aids. Specific examples of these include the resin additives described in International Publication No. 2018 / 179619.
[0037] When other components are used in the composition (X), the total content of the other components is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 15 parts by mass, based on 100 parts by mass of the polymers (A) and (B).
[0038] <Method for preparing composition (X)> The method for preparing the composition (X) is not particularly limited, and examples thereof include a method in which the polymers (A) and (B) are mixed with the other components used as necessary so as to obtain the above-mentioned contents, and then the mixture is melt-kneaded.
[0039] The method of melt-kneading is not particularly limited, and examples thereof include a method using a melt-kneading device such as an extruder. As for the conditions for melt kneading, for example, the cylinder temperature of the part of the melt kneading device where kneading is performed is usually 220 to 320° C., and preferably 250 to 300° C. When the cylinder temperature is within the above range, kneading is unlikely to be insufficient due to insufficient melting, and thermal decomposition of the polymers (A) and (B) is unlikely to occur, and a composition (X) having desired physical properties tends to be easily obtained. The kneading time during melt kneading is usually 0.1 to 30 minutes, and preferably 0.5 to 5 minutes. When the kneading time is within the above range, the polymers (A) and (B) are unlikely to undergo thermal decomposition, and melt kneading tends to be sufficiently carried out.
[0040] <Molded body> The molded article according to the present invention is formed from the composition (X) and can be obtained, for example, by molding the composition (X).
[0041] As the molding method, various known molding methods can be applied and can be appropriately selected depending on the desired application. For example, various molding methods such as injection molding, extrusion molding, injection stretch blow molding, blow molding, cast molding, calendar molding, press molding, stamping molding, inflation molding, roll molding, etc. can be mentioned. Among these, injection molding, injection stretch blow molding, and extrusion molding are preferred from the viewpoint of more effectively exerting the effects of the present invention.
[0042] The shape of the molded product is not particularly limited, and examples thereof include a film (including a sheet, a membrane, a plate, a tape, etc.), a three-dimensional molded product (including a container (including a bottle) and a tube), a rod, a fiber, a woven fabric, and a nonwoven fabric. Among these, a stretched molded product is preferred, and a film or a container (including a bottle) is more preferred, in terms of better exerting the effects of the present invention.
[0043] The molded article can be used without any limitation in applications in which a conventional 4-methyl-1-pentene polymer can be used. Examples of such uses include those described in WO 2018 / 179619. EXAMPLES
[0044] The present invention will be described below with reference to examples, but the present invention is not limited to these examples in any way.
[0045] [Production Example 1] Production of 4-methyl-1-pentene polymer A-1 In accordance with the polymerization method described in Example 3B of WO 2014 / 050817, the proportion of hydrogen used was changed so that the physical properties of the resulting polymer A-1 would be the values shown in Table 1, thereby obtaining 4-methyl-1-pentene (homo)polymer A-1.
[0046] [Production Example 2] Production of 4-methyl-1-pentene polymer B-1 At room temperature and under a nitrogen stream, 400 mL of 4-methyl-1-pentene and 0.23 mL (0.40 mmol in terms of aluminum atoms) of a hexane solution of modified methylaluminoxane (manufactured by Tosoh Finechem Co., Ltd.) (1.74 mmol / mL in terms of aluminum atoms) were charged into a SUS polymerization vessel equipped with a stirrer and the temperature was raised to 45°C. Next, 0.21 mL of a toluene solution containing 0.0005 mmol of ethylene bisindenyl zirconium dichloride that had been prepared in advance was added. Then, 695 NmL of hydrogen was charged to start polymerization. The temperature was kept at 45°C for 30 minutes from the start of the hydrogen charging. After 30 minutes had passed from the start of polymerization, the pressure was released, and then methanol was added to stop the polymerization. The reaction solution after the polymerization was stopped was poured into a mixed solution of methanol and acetone (1:2 (mass ratio) to which hydrochloric acid had been added) to precipitate the entire amount of polymer, which was then collected by filtration. The recovered polymer was then dried under reduced pressure at 80° C. for 8 hours to obtain 4-methyl-1-pentene (homo)polymer B-1. The yield was 74 g.
[0047] [Production Example 3] Production of 4-methyl-1-pentene polymer B-2 At room temperature and under a nitrogen stream, 400 mL of 4-methyl-1-pentene and 1.15 mL (2.0 mmol in terms of aluminum atoms) of a hexane solution of modified methylaluminoxane (manufactured by Tosoh Finechem Co., Ltd.) (1.74 mmol / mL in terms of aluminum atoms) were charged into a SUS polymerization vessel equipped with a stirrer and the temperature was raised to 45°C. Next, 3.1 mL of a toluene solution containing 0.005 mmol of dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride that had been prepared in advance was added. Then, 695 NmL of hydrogen was charged to start polymerization. The temperature was kept at 45°C for 30 minutes from the start of the hydrogen charging. After 30 minutes had passed from the start of polymerization, the pressure was released, and then methanol was added to stop the polymerization. The reaction solution after the polymerization was stopped was poured into a mixed solution of methanol and acetone (1:2 (mass ratio) to which hydrochloric acid had been added) to precipitate the entire amount of polymer, which was then recovered by filtration. The recovered polymer was then dried under reduced pressure at 80° C. for 8 hours to obtain 4-methyl-1-pentene (homo)polymer B-2. The yield was 38 g.
[0048] [Production Example 4] Production of Copolymer C According to the polymerization method described in Comparative Example 9 of WO 2006 / 054613, the proportions of 4-methyl-1-pentene, 1-hexadecene, 1-octadecene and hydrogen used were changed so that the physical properties of the resulting polymer were as shown in Table 1, thereby obtaining a copolymer C of 4-methyl-1-pentene, 1-hexadecene and 1-octadecene.
[0049] <Composition> The content of the structural unit (i) and the content of the structural unit (ii) in each of the polymers synthesized in the above Production Examples were measured using the following apparatus and conditions. 13 A C-NMR spectrum was obtained. 13 The chemical shifts were calculated from the C-NMR spectrum. The reference value for the chemical shifts was 27.50 ppm. The results are shown in Table 1. Here, the structural unit (i) is a structural unit derived from 4-methyl-1-pentene, and the structural unit (ii) is a structural unit derived from a copolymerizable monomer with 4-methyl-1-pentene.
[0050] Equipment: JEOL Ltd. ECP500 nuclear magnetic resonance spectrometer Solvent: o-dichlorobenzene / heavy benzene (80% by volume / 20% by volume) mixed solvent Sample concentration: 55mg / 0.6mL Measurement temperature: 120℃ Observation kernel: 13 C(125MHz) Sequence: Single pulse proton decoupling Pulse width: 4.7μsec (45° pulse) Repeat time: 5.5 seconds Number of times: 10,000 or more
[0051] <Intrinsic viscosity [η]> The intrinsic viscosity [η] of each of the polymers synthesized in the above Production Examples was measured at 135° C. using decalin as a solvent. Specifically, about 20 mg of each polymer synthesized in the above Production Examples was weighed out, dissolved in 15 mL of decalin, and the specific viscosity η sp The decalin solution was diluted with 5 mL of decalin solvent, and the specific viscosity η was measured in the same manner. sp This dilution procedure was repeated two more times, and the η sp The value of / C was calculated as the intrinsic viscosity (see the formula below). The results are shown in Table 1. [η]=lim(η sp / C) (C→0)
[0052] <Meso-dyad fraction> The meso diad fraction of each polymer synthesized in the above Preparation Examples is defined as the ratio of isobutyl branches in the same direction when any two head-to-tail bonded 4-methyl-1-pentene unit sequences in the polymer chain are expressed as a planar zigzag structure. 13 The results were calculated from the C-NMR spectrum using the following formula. The results are shown in Table 1. Mesodiad fraction (%) = [m / (m+r)] × 100 (In the formula, m and r represent the absorption intensities (integrated values) derived from the main chain methylene of the head-to-tail bonded 4-methyl-1-pentene units, which will be described later.)
[0053] 13 C-NMR spectra were measured using the following equipment and conditions. The chemical shift reference value was 128 ppm for benzene-d6. Equipment: JEOL Ltd. ECP500 nuclear magnetic resonance spectrometer Solvent: o-dichlorobenzene / benzene-d6 (volume ratio 4 / 1) mixed solvent Sample concentration: 60mg / 0.6mL Measurement temperature: 120℃ Observation kernel: 13 C(125MHz) Sequence: Single-pulse proton broadband decoupling Pulse width: 5.0 μsec (45° pulse) Repeat time: 5.5 seconds
[0054] Obtained 13 In the peak region of the C-NMR spectrum, the region from 41.5 to 43.3 ppm was divided by the minimum point of the peak profile, and the high magnetic field side was classified as the first region, and the low magnetic field side was classified as the second region. In the first region, the main chain methylene in two consecutive 4-methyl-1-pentene units shown by (m) resonates, and the integrated value when the measured polymer is regarded as a 4-methyl-1-pentene homopolymer is taken as "m". In the second region, the main chain methylene in two consecutive 4-methyl-1-pentene units, indicated by (r), resonates, and the integrated value is designated as "r". The detection limit was defined as less than 0.01%.
[0055] <Melting point (Tm)> For each of the polymers synthesized in the above Production Examples, the exothermic and endothermic curves were obtained using a DSC measuring device (DSC220C) manufactured by Seiko Instruments Inc., and the temperature at the peak position during the temperature rise was taken as the melting point (Tm). The measurement was performed as follows. About 5 mg of the polymer was packed in an aluminum pan for measurement, and the temperature was raised from 20°C to 280°C at a heating rate of 10°C / min. After holding at 280°C for 5 minutes, the temperature was lowered to 20°C at a cooling rate of 10°C / min and held at 20°C for 5 minutes. Next, the temperature was raised again from 20°C to 280°C at a heating rate of 10°C / min, and the temperature was lowered again to 50°C at a cooling rate of 50°C / min. The melting point (Tm) was determined based on the melting peak that appeared during the second heating. When there were multiple melting peaks, the higher peak temperature was taken as the melting point (Tm). The results are shown in Table 1.
[0056] [Table 1]
[0057] [Example 1] A twin-screw extruder (PCM43, manufactured by Ikegai Corporation, screw diameter: 43 mm) was charged with 80 parts by mass of the polymer A-1 obtained in Production Example 1 and 20 parts by mass of the polymer B-1 obtained in Production Example 2. The mixture was then melt-kneaded at 280° C. and a rotation speed of 200 rpm in the twin-screw extruder to obtain a polymer composition (X1).
[0058] The obtained polymer composition (X1) was injected into a 70-ton injection molding machine (M70B) manufactured by Meiki Seisakusho Co., Ltd. under the conditions of a cylinder temperature of 280°C and a mold temperature of 60°C to prepare a square plate-shaped injection test piece having a thickness of 1 mm.
[0059] [Example 2] A twin-screw extruder (PCM43, manufactured by Ikegai Corporation, screw diameter: 43 mm) was charged with 80 parts by mass of the polymer A-1 obtained in Production Example 1 and 20 parts by mass of the polymer B-2 obtained in Production Example 3. Thereafter, the mixture was melt-kneaded at 280° C. and a rotation speed of 200 rpm in the twin-screw extruder to obtain a polymer composition (X2). An injection specimen was prepared in the same manner as in Example 1, except that the obtained polymer composition (X2) was used.
[0060] [Comparative Example 1] A polymer composition (CX1) was obtained in the same manner as in Example 1, except that the polymer B-1 was not used and 100 parts by mass of the polymer A-1 obtained in Production Example 1 was used. An injection specimen was prepared in the same manner as in Example 1, except that the obtained polymer composition (CX1) was used.
[0061] [Comparative Example 2] A polymer composition (CX2) was obtained in the same manner as in Example 1, except that 90 parts by mass of the polymer A-1 obtained in Production Example 1 and 10 parts by mass of the polymer B-1 obtained in Production Example 2 were used. An injection test piece was prepared in the same manner as in Example 1, except that the obtained polymer composition (CX2) was used.
[0062] [Comparative Example 3] A polymer composition (CX3) was obtained in the same manner as in Example 1, except that 70 parts by mass of the polymer A-1 obtained in Production Example 1 and 30 parts by mass of the polymer B-1 obtained in Production Example 2 were used. An injection specimen was prepared in the same manner as in Example 1, except that the obtained polymer composition (CX3) was used.
[0063] [Comparative Example 4] A polymer composition (CX4) was obtained in the same manner as in Example 2, except that 90 parts by mass of the polymer A-1 obtained in Production Example 1 and 10 parts by mass of the polymer B-2 obtained in Production Example 3 were used. An injection specimen was prepared in the same manner as in Example 1, except that the obtained polymer composition (CX4) was used.
[0064] [Comparative Example 5] A polymer composition (CX5) was obtained in the same manner as in Example 2, except that 70 parts by mass of the polymer A-1 obtained in Production Example 1 and 30 parts by mass of the polymer B-2 obtained in Production Example 3 were used. An injection specimen was prepared in the same manner as in Example 1, except that the obtained polymer composition (CX5) was used.
[0065] [Comparative Example 6] A polymer composition (CX6) was obtained in the same manner as in Example 1, except that 80 parts by mass of Polymer A-1 obtained in Production Example 1 and 20 parts by mass of Copolymer C obtained in Production Example 4 were used. An injection specimen was prepared in the same manner as in Example 1, except that the obtained polymer composition (CX6) was used.
[0066] <Tensile test> Using the prepared injection test pieces, dumbbell-shaped test pieces (test piece type 5) were prepared in accordance with JIS K 7127:1999, and tensile tests were carried out using an Instron universal tensile testing machine 3380 at a tensile speed of 5 mm / min and a measurement temperature of 23°C to measure the tensile stress at break, tensile elongation at break, and tensile modulus of elasticity. The results are shown in Table 2.
[0067] [Table 2]
Claims
1. 75 to 85% by mass of a 4-methyl-1-pentene polymer (A) satisfying the following requirements (A-i) to (A-iii); 15 to 25% by mass of a 4-methyl-1-pentene polymer (B) satisfying the following requirements (Bi) to (B-iv); (wherein the total of polymers (A) and (B) is 100 mass%). Requirement (Ai): Consists only of structural units derived from 4-methyl-1-pentene Requirement (A-ii): Intrinsic viscosity [η] measured in decalin at 135 ° C. A is 1.0 to 5.0 dl / g Requirement (A-iii): 13 Meso-dyad fraction (m A ) is greater than 97.0% Requirement (Bi): Consists of only structural units derived from 4-methyl-1-pentene Requirement (B-ii): Intrinsic viscosity [η] measured in decalin at 135 ° C. B is 0.05 to 1.0 dl / g Requirement (B-iii): 13 Meso-dyad fraction (m B ) is 90.0 to 97.0% Requirement (B-iv): Melting point (Tm B ) is less than 220°C
2. A molded article formed from the polymer composition (X) according to claim 1.
3. The molded article according to claim 2, which is an injection molded article, an injection stretch blow molded article or an extrusion molded article.
4. The molded article according to claim 2 or 3, which is a film or a container.
Citation Information
Patent Citations
4-methyl-1-pentene polymer, resin composition, and molded object
WO2017150265A1